2021
DOI: 10.1039/d0cp06493a
|View full text |Cite
|
Sign up to set email alerts
|

Ionic-strength and pH dependent reactivities of ascorbic acid toward ozone in aqueous micro-droplets studied using aerosol optical tweezers

Abstract: The heterogeneous oxidation reaction of single aqueous ascorbic acid (AH2) aerosol particles with gas-phase ozone was investigated in this study utilizing aerosol optical tweezers with Raman spectroscopy. The measured liquid-phase...

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
58
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 17 publications
(59 citation statements)
references
References 59 publications
1
58
0
Order By: Relevance
“…Recently, Chang et al. utilized aqueous ascorbic acid micro‐droplets as prototype bioaerosols to investigate the kinetics of their reactions with gaseous ozone by means of aerosol optical tweezers [22] . They found that the reactivities of ascorbic acid in aqueous aerosols toward ozone are significantly dependent on aerosol pH and ion strength, and high acidities could significantly reduce the reactivity of ascorbic acid toward ozone.…”
Section: Motivationmentioning
confidence: 99%
See 4 more Smart Citations
“…Recently, Chang et al. utilized aqueous ascorbic acid micro‐droplets as prototype bioaerosols to investigate the kinetics of their reactions with gaseous ozone by means of aerosol optical tweezers [22] . They found that the reactivities of ascorbic acid in aqueous aerosols toward ozone are significantly dependent on aerosol pH and ion strength, and high acidities could significantly reduce the reactivity of ascorbic acid toward ozone.…”
Section: Motivationmentioning
confidence: 99%
“…They found that the reactivities of ascorbic acid in aqueous aerosols toward ozone are significantly dependent on aerosol pH and ion strength, and high acidities could significantly reduce the reactivity of ascorbic acid toward ozone. These findings suggest that the enhanced acidity of airway lining fluids due to inhaled sulfur dioxide or acidic particular matters can suppress the antioxidant activity and cause more direct contacts of atmospheric oxidants to bio‐surfaces [22] . These ascorbic acid or uric acid aerosols can also be regarded as prototype bio aerosols, and these antioxidants actually could become to protect the pathogens inside bio‐aerosols against ozone from environments for a period of time.…”
Section: Motivationmentioning
confidence: 99%
See 3 more Smart Citations